Churning power loss of the intermediate gearbox in a helicopter under splash lubrication. (January 2022) - Lu, Fengxia; Wang, Meng; Bao, Heyun; Huang, Wei; Zhu, Rupeng
Based on computational fluid dynamics, a two-phase flow model was established to calculate the churning power loss of the spiral bevel gears under splash lubrication. The error between the simulation results and experiment results is only 7.04%. Taking a certain helicopter as an example, the churning power loss of the intermediate gearbox is ∼2.6051 kW, accounting for ∼1.93% of the input power. Besides, the motion mechanisms of free flow, ejection flow and splashing flow of the spiral bevel gear were investigated. The influences of the rotational speed and oil immersion depth on the churning power loss were analysed. The rotational speed and oil immersion depth of the intermediate gearbox should be in the range of 3000–5000 r/min and 17–26 mm, respectively, which can ensure sufficient lubrication and low churning power loss.